Writing strategies used by male and female in Academic Writing activities in ELEP at UNP - Sari, Yunita; Arianto, M Affandi (Journal of English Language Teaching, 2025)
This study aimed to investigate the writing strategies used by students before, while, and after writing, as well as to examine the differences between male and female students in using these strategies during academic writing activities at the English Education Department of Universitas Negeri Padang. A descriptive quantitative research design was applied, involving 42 students who had already completed the Academic Writing course. The data were collected through a questionnaire adapted from the English Writing Strategy Inventory (Hwang & Lee, 2017) and Dari et al. (2022), which measured eight categories of writing strategies: metacognitive, cognitive, L1 use, L2 use, compensation, revision, social, and memory strategies. The findings revealed that metacognitive (M = 3.65) and cognitive strategies (M = 3.54) were the most frequently used across all stages of writing. It seems that students tended to plan, monitor, and evaluate their writing rather than rely on collaborative strategies. Regarding gender differences, most strategies showed no significant difference, although female students scored higher on Metacognitive Strategy related to rereading their paragraphs to check the logical flow during the while-writing stage (p = 0.016) and self- assessing the coherence between the supporting ideas in the after- writing (p = 0.040), indicating slightly greater reflection on text coherence and content quality. Overall, the findings suggest that writing strategies was similar across genders, likely influenced more by the shared learning environment and instruction than by gender itself.